ANALISIS KOMODITAS UNGGULAN SEKTOR PERTANIAN DATARAN TINGGI SUMATERA UTARA - Elvin Desi Martauli; sarah Gracia (Universitas 17 Agustus 1945 Samarinda, 2021)
The agricultural sector in the highlands of North Sumatra is the main sector of economic support for the people in the area. Although some sub-sectors have not shown significant improvement in the economy. For this reason, researchers are interested in analyzing each basic or superior sub-sector, so that policies can be taken to solve existing problems. The purpose of this study was to analyze the superior commodities of the upland agricultural sector in North Sumatra. The data used in the secondary data is obtained from the Central Statistics Agency (BPS) in 2019 covering the food crop sub-sector, the vegetable and fruit horticulture sub-sector, the livestock sub-sector, the plantation sub-sector. To answer the research questions, LQ analysis is used to determine superior commodities. The results showed that the food crop sub-sector in the highlands was a superior commodity with LQ = 1.62. The vegetable and fruit horticultural sub-sector is included in the basic or superior category with each value (1.13), (1.80). The plantation sub-sector has the greatest LQ value with an LQ value of 2.90. So it can be concluded that upland agricultural commodities in North Sumatra are generally the base agricultural sector.